CHEMICAL STRUCTURE OPTIMIZATION OF LUPEOL AS ER-Α AND HER2 INHIBITOR - Pratama, Mohammad Rizki Fadhil; S, Sutomo (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Lupeol, a triterpenoid isolated from Kasturi (Mangifera casturi) fruit has been known for having several pharmacological activities, including anticancer properties. Lupeol showed antiproliferative activity toward many cancer cells line including breast cancer. Lupeol showed promising potency as both ER-α and HER2 inhibitors, although still lower than known ER-α and HER2 Inhibitors. Chemical structure optimization of lupeol was predicted could increase the affinity of lupeol derivatives against ER-α and HER2. This study aims to determine lupeol derivative with the highest affinity against ER-α and HER2. Methods: All ligands were sketched and optimized using Gaussian 03W with Hartree–Fock method basis set 3-21G. Molecular docking was performed using Autodock 4.2.6 on several modified chemical structure of lupeol against active site of ER-α and HER2. The main parameter used was the free energy of binding and inhibition constants as affinity marker. Results: The docking results show that lupeol derivative with an amine group (Lupeol-2) and ethyl group (Lupeol-4) at position C3 provide the highest affinity with the free energy of binding and dissociation constant −12.24 kcal/mol and 1.07 nM for ER-α also −9.63 kcal/mol and 86.94 nM for HER2, respectively. Interestingly, although lupeol derivatives showed higher affinity toward ER-α, their amino acid residues were closer to the interaction on HER2. Conclusion: These results predict that lupeol have greater potential to be developed as a HER2 inhibitor. Further, derivate lupeol-4 should be potential to be developed as HER2-positive breast cancer therapy.